Orogenic Growth of the Fuegian Andes (52–56°) and Their Relation to Tectonics of the Scotia Arc - Ghiglione, Matias
The tectonic evolution of the Fuegian Andes is strongly related to their southern neighbors, the Scotia Sea and Antarctica. During Mesozoic times, extensional and magmatic processes in the southernmost Andes developed in continuity with the Antarctic Peninsula. The Rocas Verdes back-arc oceanic basin opened during the Jurassic along the Patagonian?Fuegian margin, widening toward the south were it connected with the Weddell Sea. Jurassic volcaniclastic deposits from the large igneous province Chon Aike of Patagonia and the Antarctic Peninsula Volcanic Group were part of the same volcanic event related to Gondwana breakup. It was followed by Late Cretaceous compression, closure and inversion of the Rocas Verdes Basin that culminated with the onset of orogenesis and foreland sedimentation in the Austral or Magallanes Basin. The beginning of compression coincided with geodynamic reconstructions predicting the collision of the Antarctic Peninsula against the Fuegian Andes due to accelerated convergence rates. Afterward, three phases of Cenozoic deformation in the southernmost Andes can also be tied to tectonics of the Scotia Arc: (1) a Paleocene?Early Eocene continental stretching on the Austral, Malvinas, and South Malvinas basins, produced by the slow, N?S separation of South America and Antarctica. After 50 Ma, crustal extension was concentrated in the Drake Passage due to an acceleration in South America?Antarctica separation rate, while regional continental stretching ceased. (2) The Fuegian Andes were affected by Middle Eocene?Oligocene compressional deformation producing the forward advance of theorogenic front. Shortening was due to the synergetic combination of rapid convergence and northward directed subduction of the Farallon plate against South America, and the fast opening of the Scotia Sea associated with ridge-push forces. (3) The development of the present seismically active Magallanes?Fagnano continental strike-slip plate boundary between South America and Scotia Plates produced widespread ...